The surgical management of complicated peptic ulcer disease: An EAST video presentation. Issue 1 (1st July 2022) - Hudnall, Aaron; Bardes, James M.; Coleman, Kennith; Stout, Conley; Regier, Daniel; Balise, Stephen; Borgstrom, David; Grabo, Daniel
Abstract : Surgical management of peptic ulcer disease including laparoscopic and open Graham patch, GDA ligation and vagotomy and antrectomy. #ulcerdisease #perforatedulcer #ulcer #ulcersurgery #gastricperforation #duodenalperforation Abstract : BACKGROUND: Peptic ulcer disease (PUD), once primary a surgical problem, is now medically managed in the majority of patients. The surgical treatment of PUD is now strictly reserved for life-threatening complications. Free perforation, refractory bleeding and gastric outlet obstruction, although rare in the age of medical management of PUD, are several of the indications for surgical intervention. The acute care surgeon caring for patients with PUD should be facile in techniques required for bleeding control, bypass of peptic strictures, and vagotomy with resection and reconstruction. This video procedures and techniques article demonstrates these infrequently encountered, but critical operations. CONTENT (VIDEO DESCRIPTION): A combination of anatomic representations and videos of step-by-step instructions on perfused cadavers will demonstrate the key steps in the following critical operations. Graham patch repair of perforated peptic ulcer is demonstrated in both open and laparoscopic fashion. The choice to perform open versus laparoscopic repair is based on individual surgeon comfort. Oversewing of a bleeding duodenal ulcer via duodenotomy and ligation of the gastroduodenal artery is infrequent in the age of advanced endoscopy and interventional radiology techniques, yet this once familiar procedure can be lifesaving. Repair of giant duodenal or gastric ulcers can present a challenging operative dilemma on how to best repair or exclude the defect. Vagotomy and antrectomy, perhaps the least common of all the aforementioned surgical interventions, may require more complex reconstruction than other techniques making it challenging for inexperienced surgeons. A brief demonstration on reconstruction options will be shown, and it includes Roux-en-Y gastrojejunostomy. CONCLUSION: Surgical management of PUD is reserved today for life-threatening complications for which the acute care surgeon must be prepared. This presentation provides demonstration of key surgical principles in management of bleeding and free perforation, as well as gastric resection, vagotomy and reconstruction. LEVEL OF EVIDENCE: Video procedure and technique, not applicable. Abstract :